In situ synthesis of Pt/carbon nanofiber nanocomposites with enhanced electrocatalytic activity toward methanol oxidation - Wang, D.; Liu, Yang; Huang, J.; You, T. (Academic Press, 2012)
Pt/carbon nanofiber (Pt/CNF) nanocomposites were facilely synthesized by the reduction of hexachloroplatinic acid (H2PtCl6) using formic acid (HCOOH) in aqueous solution containing electrospun carbon nanofibers at room temperature. The obtained Pt/CNF nanocomposites were characterized by TEM and EDX. The Pt nanoparticles could in situ grow on the surface of CNFs with small particle size, high loading density, and uniform dispersion by adjusting the concentration of H2PtCl6 precursor. The electrocatalytic activities of the Pt/CNF nanocomposites were also studied. These Pt/CNF nanocomposites exhibited higher electrocatalytic activity toward methanol oxidation reaction compared with commercial E-TEK Pt/C catalyst. The results presented may offer a new approach to facilely synthesize direct methanol fuel cells (DMFCs) catalyst with enhanced electrocatalytic activity and low cost.